Journey to upcycling: Understanding consumer's behavior regarding clothing disposal in Lima Centro, Peru - Joana Delgado Vásquez, Irina (2024)
In the districts located in Lima Centro, there is an issue regarding the generation of post-consumer textile waste and a trend towards consumerism among the population. In this context, the aim of the study was to conduct a diagnosis on the behaviours of individuals identified as female, regarding the frequency of garment acquisition, the lifespan they attribute to them, the predominant actions for their disposal, and their willingness to donate obsolete garments for upcycling. Surveys and focus groups were conducted with individuals identified as female, revealing that 38.44% purchase clothing monthly. Additionally, 51.17% assign a lifespan of less than or equal to one year to their garments. Moreover, the most common disposal action was keeping in residence, preferred by 56.88% of the surveyed individuals. The results indicated that people do not exhibit appropriate and sustainable behaviour in their clothing purchase and disposal habits, representing a significant challenge for potential valorization strategies to be implemented, including upcycling.